Pengaruh Advertising Dan Special Event Terhadap Peningkatan Brand Awareness - Anwar, Rima Rahmani; Anggraini T., Rosita (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The right communication to grow brand awareness can be realized through advertising. In addition, events are one of the strategies to have a positive influence in communicating a brand. This study wants finding out how building and increasing brand awareness through advertising on social media Instagram and the "Zumba party" event. This research was conducted at the KALCare Lotte Shopping Avenue outlet using a quantitative approach and a positivism paradigm. The study population was 61 “Zumba party” participants as well as a representative sample. The data was processed with SPSS 20.1. then analyzed using Cronbach's Alpha value test factor analysis and t test for regression test The results showed that the "Zumba party" event had a strong enough influence to increase brand awareness of PT. Kalbe Farma. As for advertising on Twitter, although not significant, it still has an influence to increase brand awareness of PT. Kalbe Farma in low levels. Thus, advertisements on the @kalcare Instagram account should be maximized in terms of content and frequency in communicating the Kalbe Farma brand in order to be able to grow Brand Awareness. Then for further research to expand the findings of the benefits of advertising and special events in growing Brand Awareness to customers in various industries and also among society in general.